ANALISIS KEPUASAN KONSUMEN TERHADAP ATRIBUT BUAH PISANG KEPOK (Studi Kasus Konsumen di Tiga Kota Kuala Pembuang, Sampit, dan Palangkaraya) - PERMADI, ROKHMAN (Jurnal Social Economic of Agriculture, 2015)
The objectives of the research were to analyze the characteristics and satisfaction of consumers towards the attributes of bananas Kepok in Kuala Pembuang, Sampit and Palangkaraya. The research method used is descriptive qualitative method and the sampling technique with accidental sampling of the 150 respondents were divided in Kuala Pembuang, Sampit and Palangkaraya each 50 respondents. Variable that will be analyzed include: attributes of price, taste, freshness, ripeness, size, shape, color, and skin hygiene using Importance-Performance Analysis (IPA) and Consumers Satisfaction Index (CSI). Based on the results of a study of the characteristics of the respondents in the city of Kuala Pembuang, Sampit and Palangkaraya in the range of ages is relatively uniform and still relatively productive age of 20-50 years of age. Different when viewed in terms of the education level of respondents in the city of Sampit and Palangkaraya more respondents who have been through higher education compared to respondents in the city of Kuala Pembuang. Moreover, if it is seen by the income level of the respondents in Kuala Pembuang inclined relatively lower income compared to respondents in the city of Sampit and Palangkaraya. The score of satisfaction index each city shows the satisfaction of respondents to attribute banana Kepok satisfied to the value in each city is 0,7151 (Kuala Pembuang), 0,7023 (Sampit) and 0,7439 (Palangkaraya).